University - Community relationship: Expression of Social Responsibility of its Protagonists - Garbizo Flores, Noraida (2020)
The vision of universities in the field of social responsibility has made it a reference institution in the community, promoting relationships, alliances and dialogues of knowledge, blurred of traditional notions that accentuate the exclusive role of inward training of the university grounds. From this analysis perspective, it is about assuming the university-community link as a support for the integral formation of the student and articulating axis of their substantive processes. Given the recognition of this transcendent relationship, the article aims to carry out a conceptual review and critical analysis of the university-community nexus, expression of social responsibility of its protagonists, with the use of the historical-logical method and the help of documentary analysis. The findings aim to highlight the university-community link as scenarios par excellence in the comprehensive training of professionals, citizens and people committed to the sustainable development of the community environment.